2019
DOI: 10.2147/ceg.s186393
|View full text |Cite
|
Sign up to set email alerts
|

<p>Propofol sedation in colonoscopy: from satisfied patients to improved quality indicators</p>

Abstract: Background Propofol-mediated sedation is safe and clearly associated with increased patient satisfaction. However, whether it results in a favorable effect on colonoscopy outcomes and performance compared to standard sedation with benzodiazepines/opiates remains unclear. Objectives To determine the effect of propofol-mediated sedation on colonoscopy-quality measures compared to traditional sedation. Methods A large cohort of 44,794 patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 22 publications
(22 reference statements)
0
21
0
Order By: Relevance
“…However, there is still much controversy surrounding the effect of sedation on quality of colonoscopy. Some previous studies showed that patients who received sedation were more likely to have an enhanced CIR [ 23 26 ], but the other study demonstrated similar rates of cecal intubation among sedated and unsedated colonoscopy [ 27 ]. In our results, the colonoscopy with sedation was significantly associated with higher CIR when controlling for other patient and endoscopist factors, which confirms positive results from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still much controversy surrounding the effect of sedation on quality of colonoscopy. Some previous studies showed that patients who received sedation were more likely to have an enhanced CIR [ 23 26 ], but the other study demonstrated similar rates of cecal intubation among sedated and unsedated colonoscopy [ 27 ]. In our results, the colonoscopy with sedation was significantly associated with higher CIR when controlling for other patient and endoscopist factors, which confirms positive results from previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Power spectra (dB) were computed over 2-minute long epoch of EEG, partitioned into 512-point epochs, and averaged, yielding a temporal resolution of 2 Hz. Normalized power was calculated as the fraction of a specific frequency power, including delta (0.5-4 Hz), theta (4-8 Hz), alpha (8-12 Hz), spindle (12)(13)(14)(15), beta (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) and gamma (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), in the total power over all frequency bands from 0.5-40 Hz. The mean powers in percent for pre (1), post saline or caffeine injection (2), during 1.2% isoflurane (3) and before RORR (4) were computed by the MATLAB program.…”
Section: Power Spectramentioning
confidence: 99%
“…Our earlier studies in rats showed that caffeine was equally effective at accelerating emergence from propofol anesthesia as it was in isoflurane anesthesia [15]. Light propofol anesthesia is commonly used in a variety of procedures including colonoscopies and to prevent movement in MRI exams [18][19][20][21]. It will be important to determine whether caffeine can reverse the effects of other anesthetics, like propofol and dexmedetomidine, in a similar manner to that observed for isoflurane, as these drugs and their effects can stay in the body long after the termination of the anesthetic agent.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Airway management is, therefore, vital to avoid airway obstruction and associated respiratory complications. [ 3 ]…”
mentioning
confidence: 99%